2011
DOI: 10.1088/2041-8205/740/1/l21
|View full text |Cite
|
Sign up to set email alerts
|

A Uniform Correlation Between Synchrotron Luminosity and Doppler Factor in Gamma-Ray Bursts and Blazars: A Hint of Similar Intrinsic Luminosities?

Abstract: We compile 23 Gamma-ray Bursts (GRBs) and 21 blazars with estimated Doppler factors, and the Doppler factors of GRBs are estimated from their Lorentz factors by assuming their jet viewing angles θ → 0 o . Using the conventional assumption that the prompt emission of GRBs is dominated by the synchrotron radiation, we calculate the synchrotron luminosity of GRBs from their total isotropic energy and burst duration. Intriguingly, we discover a uniform correlation between the synchrotron luminosity and Doppler fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
8
26
0
Order By: Relevance
“…Wang & Wei (2011) compared the spectral properties of blazars and optically bright GRB afterglows, and found that GRB afterglows have the same radiation mechanism as BL Lac objects. A similar correlation between the synchrotron luminosity and Doppler factor of GRBs and AGNs has been found (Wu et al 2011). Nemmen et al (2012 suggested that the relativistic jets in AGNs and GRBs have similar energy dissipation efficiencies.…”
Section: Introductionsupporting
confidence: 79%
“…Wang & Wei (2011) compared the spectral properties of blazars and optically bright GRB afterglows, and found that GRB afterglows have the same radiation mechanism as BL Lac objects. A similar correlation between the synchrotron luminosity and Doppler factor of GRBs and AGNs has been found (Wu et al 2011). Nemmen et al (2012 suggested that the relativistic jets in AGNs and GRBs have similar energy dissipation efficiencies.…”
Section: Introductionsupporting
confidence: 79%
“…The similar slopes of the GRB/blazar sample and the pure GRB sample strengthen that the correlations as found in GRBs can be extended to blazars. These results provide new similarities on the jet physics in GRBs and blazars, where several other similar properties have been found in last several years(e.g., Wang & Wei 2011;Wu et al 2011;Nemmen et al 2012). It should be noted that Sonbas et al (2014) found a knee-like feature in both MTS − Γ and MTS − Lγ correlations, where the anti-correlations become flat for Γ 225 or Lγ 10 51 erg/s.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…The high-energy index β ranges from 2 to 3 with an average value of 2.6 (e.g., Tang et al 2015) in the Band function of GRBs (e.g., Band et al 1993) and β ∼ 2 − 3 for blazars as derived from the indices of electron distribution above the broken electron Lorentz factor in modeling their multi-waveband SEDs (e.g., p2 ∼ 3 − 5, Kang et al 2014). Wu et al (2011) found a universal correlation between synchrotron luminosity, Lsyn, and Doppler factor, D, in GRBs and blazars (Lsyn ∝ D 3.1±0.1 ), where the prompt emission of GRBs and the first hump of blazars are assumed to be dominated by synchrotron emission. Assuming gamma-ray luminosities in the second hump is normally more or less similar to Lsyn of the first hump in blazars and D ∼ 2Γ for the relativistic jet with viewing angle θ → 0 o , we find Lγ ∝ Γ 3.1±0.1 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Note, however this GRB Figure 3. The plot of Doppler factor vs isotropic equivalent luminosity for GRBs and blazars using Wu et al (2011). The red dot with errors is GRB 170817A.…”
Section: Methods and Resultsmentioning
confidence: 99%